2017
DOI: 10.1007/s11524-016-0115-0
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Safety in the Age of the Opioid Crisis: Needle Stick Injury among Baltimore Police

Abstract: At a time of resurgence in injection drug use and injection-attributable infections, needle stick injury (NSI) risk and its correlates among police remain understudied. In the context of occupational safety training, a convenience sample of 771 Baltimore city police officers responded to a self-administered survey. Domains included NSI experience, protective behaviors, and attitudes towards syringe exchange programs. Sixty officers (8%) reported lifetime NSI. Officers identifying as Latino or other race were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 7 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…Worldwide, law enforcement has negatively impacted PWID willingness to purchase and carry sterile syringes, avoidance of sharing syringes and shooting galleries, and utilization of syringe exchange programs [ 21 – 35 ]. Police confiscation of both used and unused syringes negatively influences the way PWID consume drugs [ 4 , 8 , 10 , 13 17 , 23 , 36 48 ]. In addition to the negative health outcomes of incarceration in terms of infectious disease transmission, overdose, and structural vulnerability risk [ 49 , 50 ], arrests for syringe possession constitute a human rights and global health concern that may cause immediate and downstream harm to PWID.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Worldwide, law enforcement has negatively impacted PWID willingness to purchase and carry sterile syringes, avoidance of sharing syringes and shooting galleries, and utilization of syringe exchange programs [ 21 – 35 ]. Police confiscation of both used and unused syringes negatively influences the way PWID consume drugs [ 4 , 8 , 10 , 13 17 , 23 , 36 48 ]. In addition to the negative health outcomes of incarceration in terms of infectious disease transmission, overdose, and structural vulnerability risk [ 49 , 50 ], arrests for syringe possession constitute a human rights and global health concern that may cause immediate and downstream harm to PWID.…”
Section: Introductionmentioning
confidence: 99%
“…Police encounters with PWID involving syringes may also have a negative health impact on police officers [ 5 , 6 , 36 , 51 57 ]. In 1996, among 803 participants in the San Diego Police Department, 29.7% had at least one needle stick injury (NSI) ever, of which 27.7% had had two or more; only 39.2% sought medical attention for the NSI [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found that younger age (20-29 years) and having 4-10 years of service were associated with a higher risk of transcutaneous exposures (needlestick injuries and human bites) [Pagane et al 1996]. More recent survey studies in North Carolina and Baltimore, Maryland have documented that 3.8%-8% of police officers reported ever having a needlestick injury and a rate of 36-58 needlestick injuries per 10,000 officer-years (or 3.6-5.8 needlestick injuries per 1,000 officer-years) [Cepeda et al 2017;Davis et al 2014]. …”
Section: Blood Contact With Skin (Unknown If Intact) †mentioning
confidence: 99%